The relationship between visual and verbal codes of visual rhetoric in a sequential art setting - Van der Merwe, Ernest (My University, 2007)
The aim of the study was to examine the relationship between visual and verbal codes of visual rhetoric in a sequential art setting. The literature investigation component of the study covered: (1) the notion of visual literacy; (2) the principles of visual rhetoric, and (3) trends in sequential art. The empirical component of the study involved the production of sequential art test material with an accompanying questionnaire in order to measure the comprehension of visual rhetoric in a sample of 197 undergraduate students at the Vaal University of Technology. The working hypotheses that guided the study were, firstly, that the comprehension of the visual code of the visual rhetoric used in a sequential art setting differs between (a) study participants that received visual training prior to the data collection and (b) study participants that received no visual training prior to the data collection, and secondly, that the comprehension of the visual code of the visual rhetoric used in a sequential art setting differs between (a) study participants that received test material in their home language and (b) study participants that did not receive the test material in their home language. Following a one-way ANOVA analysis of the questionnaire data, the first hypothesis indicated a significant statistical difference (p=O.OO) and was not rejected. The second hypothesis indicated no significant statistical difference (p=0.138) and was rejected. Based on the result obtained, possibilities for further research were motivated.
Thesis (M. Tech.) - Dept. of Visual Arts and Design, Faculty of Human Sciences - Vaal University of Technology
Keywords: Visual rhetoric; Visual codes; Verbal codes; Visual literacy; 701.8; Visual communication -- Art.; Visual literacy; Verbal ability; Narrative art; Comic books, strips, etc.